Effects of variety and storage duration on the nutrient digestibility and the digestible and metabolisable energy content of maize fed to growing pigs. Issue 1 (2nd January 2017) - Zhang, Lei; Liu, Ling; Li, Defa; Li, Quanfeng; Piao, Xiangshu; Thacker, Philip A.; Brown, Michael A.; Lai, Changhua
ABSTRACT: The objective of this research was to determine the effects of variety and storage duration on the nutrient digestibility and the digestible (DE) and metabolisable (ME) energy content in maize when fed to growing pigs. Four maize varieties (LS1, LS2, LS3 and LS4) were hand-harvested from the same growing area in China in early October of 2012. The samples were sun dried to about 14% moisture content and then stored in the warehouse of the Fengning Pig Experiment Base at China Agricultural University for 0, 3 or 10 months. Twenty-four barrows of about 33 kg body weight were used and allotted to a completely randomised block design with four diets and six replicate pigs per diet. Pigs were individually housed in metabolic crates. The four experimental diets were formulated by mixing 96.8% of each variety of maize with 3.2% vitamins and minerals. A 5-day collection period followed a 7-day diet acclimation period. The results indicated that the DE and ME contents of maize and the apparent total tract digestibility (ATTD) of organic matter (OM), dry matter, gross energy (GE), neutral detergent fibre, acid detergent fibre (ADF), crude protein (CP) and ether extract (EE) were significantly ( p  < 0.05) influenced by maize variety and storage duration. With an extension of storage duration from 0 to 10 months, the DE and ME of maize and the ATTD of OM, GE, ADF, CP and EE changed in a quadratic manner ( p  < 0.05), and 3 months of storage exceeded 0 months of storage by 1.84%, 1.43%, 0.31%, 0.32%, 15.37%, 2.11% and 5.02%, respectively. The DE, ME of maize and the ATTD of OM, GE, ADF, CP and EE decreased by 3.67%, 6.00%, 0.97%, 1.40%, 30.54%, 3.92% and 20.93%, respectively, at 10 months of storage compared to 3 months of storage. No interaction was observed between maize variety and storage duration in DE and ME contents in maize. In conclusion, under the conditions of this study, most of the nutrient digestibility and the DE and ME contents of maize increased from 0 to 3 months and decreased from 3 to 10 months.